ENTREPRENEURSHIP EDUCATION AND VENTURE INITIATIVES AMONG UNIVERSITY GRADUATES IN NORTHEASTERN NIGERIA - Jibir, Adamu; Abdu, Musa; Bala Sani, Fatima; Bello, Farida (African Journal of Social and Behavioural Sciences, 2024)
This study explores the impact of entrepreneurship education on the venture initiatives of university graduates in Northeastern Nigeria, focusing on graduates’ readiness to engage in business, venture size, and business intentions. Northeastern Nigeria, which includes states such as Adamawa, Bauchi, Borno, Gombe, Taraba, and Yobe, has faced economic and social challenges due to prolonged insurgency, with high graduate unemployment despite annual outputs of over 600,000 graduates in Nigeria. Given this context, the study examines the role of entrepreneurship education in fostering entrepreneurial intentions among graduates residing in the region. Using a structured questionnaire adapted from the Global Entrepreneurship Monitor and other sources, data was collected from a representative sample of 1,200 graduates across Bauchi, Gombe, and Taraba states. Probit and negative binomial regression models were employed to analyze the data, assessing the influence of variables such as entrepreneurship theoretical knowledge, practical skills, and personal entrepreneurial characteristics on venture engagement. The findings reveal that while male graduates and those with high practical skills show a greater tendency to engage in ventures, other factors like age, educational background, and satisfaction with the entrepreneurship education structure also significantly impact graduates’ entrepreneurial actions. Graduates from fields such as arts, social sciences, and sciences display varying levels of engagement, influenced by their educational experiences. The results highlight the importance of aligning entrepreneurship education with practical skills development to encourage graduates’ active participation in ventures, thereby addressing unemployment in Northeastern Nigeria.